Advancing the critical potential of global citizenship education in a conflict society: A study of the primary social sciences curriculum in Northern Cyprus - Kuter, Sitkiye (Elsevier Sci Ltd, 2025)
Rapid globalization and the ever-increasing global and social problems, including migrations, climate crisis and violence all around the world, penetrate, directly or indirectly, the lives of individuals and societies in diverse ways. The challenges that have arisen from these phenomena necessitate tackling democracy and education from a broader perspective. At this point, global citizenship education holds a significant position in empowering learners to act as transformative agents starting from early ages and contribute to local and global communities. This study aims to examine the primary social sciences curriculum in Northern Cyprus in terms of critical global citizenship education competencies. It employed Fairclough's three-dimensional conception of discourse analysis to critically examine the dynamic between the core curriculum and the components of social life, non-discursive world (Fairclough, 1995, 2003). The findings revealed that the learning outcomes in the social sciences curriculum were designed to cultivate students' conceptual knowledge and moral development with an emphasis on developing their higher order thinking skills; however, this was largely confined to local and national contexts and primarily grounded in knowledge transmission. The findings also indicate the competencies in which the program limits students' development of critical global citizenship. Grounded in the principles of critical global citizenship education, the findings further suggest pathways for transformative curriculum improvement.
Keywords: Global citizenship education; Social sciences curriculum; Critical perspective; Northern Cyprus